GNA13 promotes brain metastasis of non-small cell lung cancer and EMT through the WNT/β catenin signaling pathway - Wu, Jia-Qi; Zou, Han-Peng; Fan, Ruo-Yue; Cai, Jing; Wei, Ping; He, Ming-Fang; Xiang, Jin (Frontiers in Cell and Developmental Biology, 2025)
BackgroundBrain metastasis (BM) remains a major challenge in non-small cell lung cancer (NSCLC) treatment, with poorly understood mechanisms.MethodsA zebrafish xenograft model was established using the H1299 cell line to study NSCLC BM. RNA-Seq identified differentially expressed genes (DEGs) in metastasized to brain vs. non-metastasized cells. Clinical relevance of DEGs was validated using The Cancer Genome Atlas (TCGA) and Kaplan-Meier survival analysis. The anti-proliferation, migration, and invasion effects of GNA13 were also detected using CCK8 assay, scratch wound healing assay, and transwell assay in vitro. The in vivo effects of GNA13 in proliferation and migration were further examined in zebrafish embryos. Additionally, real-time quantitative PCR (RT-qPCR) and Western Blot were performed to validate and explore the underlying molecular mechanisms.ResultsThrough comprehensive RNA-Seq analysis of zebrafish xenograft model, we identified 177 DEGs significantly associated with NSCLC BM. KEGG and GO enrichment identified GNA13 as a key mediator in NSCLC BM. Clinical correlation analysis confirmed that GNA13 expression was associated with NSCLC BM and poor prognosis in lung cancer patients. Functional validation revealed that GNA13 knockdown reduced H1299 cell viability, migration, and invasion, whereas overexpression in A549 cells increased viability migration, and invasion in vitro. These in vitro findings were further validated in vivo, where GNA13 overexpression promoted tumor proliferation and metastatic potential. GNA13 was shown to activate the Wnt/β-catenin signaling pathway and induce epithelial-mesenchymal transition (EMT), thereby enhancing the metastatic potential of lung cancer cells.ConclusionThis study identifies GNA13 as a key gene of lung cancer BM. GNA13 promotes EMT and enhances the proliferation and metastatic capacity of lung cancer cells by activating the Wnt/β-catenin signaling pathway. These findings suggest that GNA13 may serve as a potential therapeutic target for preventing or treating BM in NSCLC.